2022
DOI: 10.1111/jfbc.14250
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective and hepatoprotective activity of Lepidium draba L. extracts on oxymetholone‐induced oxidative stress in rat

Abstract: Oxymetholone (OM -2-hydroxymethylene-17α-methyl-4,5α-dihyd rotestosterone) is a member of the family of anabolic androgenic steroids (AAS) and testosterone analogs, which can cause many side effects, including gynecomastia, amenorrhea, cholesterol elevation, hepatoadenoma, hepatitis, liver cancer, cholestasis, liver and kidney toxicity, even at therapeutic doses (<5 mg/kg). Due to its hepatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In this study, dilated congested blood vessels appeared between the tubules in the oxymetholone-treated group. This finding was attributed to oxymetholone toxicity [ 4 , 36 ]. Additionally, basal insertion of sperm in between spermatogenic cells may be due to rapid disruption of the junctions between Sertoli and germ cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, dilated congested blood vessels appeared between the tubules in the oxymetholone-treated group. This finding was attributed to oxymetholone toxicity [ 4 , 36 ]. Additionally, basal insertion of sperm in between spermatogenic cells may be due to rapid disruption of the junctions between Sertoli and germ cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that oxymetholone was associated with oxidative stress and cellular damage in many organs, particularly the kidney and the liver [ 4 ], as well as inducing disturbances in the testicular enzymes and hormones [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…ALOF extract was received, and the procedure was similar to the previous step. Finally, the lowest dose in which toxic symptoms or death were observed ( D L ), along with the highest dose ( D S ) in which rats did not have any toxic symptoms, were placed in the following formula and LD 50 of ALOF extract was calculated (Feng et al, 2022). normalLD50goodbreak=)(DLgoodbreak×DS…”
Section: Methodsmentioning
confidence: 99%